(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article determines structure and distinguishes word-building meanings of a typical word-building paradigm of adjective-motivated confixal verbs which mean changes in quality of an object. It is cleared out that derivatives motivated by these verbs belong to three word-building zones (substantive, verbal and adjectival); within each zone different quantity of semantic shades is underlined and a set of word-building devices realizing them is distinguished.